Analyses of Combining Ability and Genotype‐By‐Environment Interaction of Quality Protein Maize Inbred Lines Adapted to Tropical‐Highlands. Issue 6 (6th October 2016) - Abakemal, Demissew; Shimelis, Hussein; Derera, John
Abstract : Production of quality protein maize ( Zea mays L., QPM) is an economic and sustainable approach that can help to alleviate protein deficiency in developing countries. However, QPM cultivars with high grain yield and wide adaptation to the tropical‐highland subhumid maize agroecologies are yet to be developed and released for farmers. The objectives of this study were, therefore, to determine the magnitude of heterosis and combining ability of elite QPM inbred lines and to establish the genotype‐by‐environment interaction (GEI) of experimental hybrids for cultivar development and recommendation. Twelve parent half‐diallel crosses were produced, and 66 experimental hybrids were developed. The hybrids and two commercial hybrid checks were evaluated under the rainfed conditions of six tropical highland environments using an α lattice (0, 1) design during 2012 and 2013. Significant GEI was observed both in per se performances and genetic analyses. Inbred lines such as KIT32, FS60 and 142–1‐EQ were good general combiners for grain yield. Inbred line FS60 exhibited good general combining ability for reduced days to anthesis and desirable plant and ear height. Inbred line FS60 is genetically complementary to KIT32 and 142–1‐EQ and is useful for QPM hybrid cultivar development. The best hybrids identified through both combining ability and GEI analyses were KIT32 × 142–1‐EQ and 142–1‐EQ × CML144, yielding 10.3 Mg ha −1 and 9.6 Mg ha −1, respectively, across variable environments. These hybrids could be used as potential QPM single‐cross testers for three‐way hybrid cultivar development targeting tropical‐highland agroecologies.